Underline Causes and Damage Assessment of Landslide Hazards in Bangladesh: A Case of 2017 event in Rangamati District - M.N. Islam; M.M. Islam (International Association of Lowland Technology, 2020)
Landslide hazard has become a burning issue for Bangladesh that is occurring about every year and causes physical, environmental, economic and social damage with a lot of death and causalities. In last 50 years Bangladesh has lost more than 600 people in landslide hazards. This death toll is increasing day by day as in 2007, 2008, 2010, 2012, 2017 it has lost 135, 43, 60, 115, 163 lives respectively. In June 2017 landslide hazards of Chittagong division have resulted in 160 deaths and 234 injured. Most of the damages occurred in Rangamati district in the last landslide event as it has detached for one month from other districts and lost 120 people that’s why Rangamati district has been selected as the study location. The present study attempts to identify the physical and human induced causes of landslide hazards and damage assessment. Through household survey including Participatory Rural Appraisal (PRA) and Focused Group Discussions (FGDs) found that rainfall, weak soil structure, earthquake are the physical causes and hill cutting, deforestation, wrong cultivation systems, leakage in water pipe, unplanned urbanization are the major causes of landslide. Landslide in Bangladesh also occurs in specific time from June to August month of the year